Mutant HSPB1 overexpression in neurons is sufficient to cause age-related motor neuronopathy in mice - Amit K. Srivastava; Samantha R. Renusch; Nicole E. Naiman; Shuping Gu; Amita Sneh; W. David Arnold; Zarife Sahenk; Stephen J. Kolb (Neurobiology of Disease, 2012)
The small heat shock protein HSPB1 is a multifunctional, α-crystallin-based protein that has been shown to be neuroprotective in animal models of motor neuron disease and peripheral nerve injury. Missense mutations in HSPB1 result in axonal Charcot–Marie–Tooth disease with minimal sensory involvement (CMT2F) and distal hereditary motor neuropathy type 2 (dHMN-II). These disorders are characterized by a selective loss of motor axons in peripheral nerve resulting in distal muscle weakness and often severe disability. To investigate the pathogenic mechanisms of HSPB1 mutations in motor neurons in vivo, we have developed and characterized transgenic PrP-HSPB1 and PrP-HSPB1(R136W) mice. These mice express the human HSPB1 protein throughout the nervous system including in axons of peripheral nerve. Although both mouse strains lacked obvious motor deficits, the PrP-HSPB1(R136W) mice developed an age-dependent motor axonopathy. Mutant mice showed axonal pathology in spinal cord and peripheral nerve with evidence of impaired neurofilament cytoskeleton, associated with organelle accumulation. Accompanying these findings, increases in the number of Schmidt–Lanterman incisures, as evidence of impaired axon–Schwann cell interactions, were present. These observations suggest that overexpression of HSPB1(R136W) in neurons is sufficient to cause pathological and electrophysiological changes in mice that are seen in patients with hereditary motor neuropathy.